The antecedents of organizational commitment an investigation of retail employees - Tuğmaner, Ayşeseren (My University, 2004)
The aim of the study is to investigate work and company related antecendents of employee commitment mainly of retail employees using Meyer&Allen's three-component organizational commitment model. Demographic factors such as age, gender, sex, education and tenure are included in the study as moderators. The measurements are made by The Organizational Commitment Questionnaire developed by Meyer & Allen (1997) and Retention Questionnaire developed by the researcher. Study focused on frontline employees dealing with customers. 143 retail sales staff from 7 different retail firms from restaurant, supermarket, fuel, textile and entertainment sectors participated in the study. After analysing the data organizational commitment was grouped into two different forms namely emotional and continuance forms of commitment. The results have shown that company culture and value given to the employee have effect on emotional organizational commitment. The results also indicated that demographic variables asuch as age, tenure and gender has a moderating effect between retention factors and different forms of commitment. Araştırmanın amacı Meyer ve Allen'ın (1997) geliştirmiş olduğu üçlü örgütsel bağlılık modelini kullanarak perakende çalışanlarının örgütsel bağlılığını sağlayan öncülleri araştırmaktır. Yaş, cinsiyet, eğitim ve kıdem gibi demografik faktörler çalışmada moderatör olarak kullanılmıştır. Ölçüm araçları olarak Meyer ve Allen'ın geliştirmiş olduğu Örgütsel Bağlılık Ölçeği ve araştırmacı tarafından geliştirilen bağlılık öncülleri ölçeği kullanılmıştır. Çalışma, görevleri yüz yüze müşterilerle ilgilenmek olan en ön saha çalışanlarını içermektedir. Restoran, süpermarket, akaryakıt, tekstil ve eğlence sektöründen 7 farklı firmanın 143 çalışanı araştırmaya katılmıştır. Verilerin analiz edilmesinden sonra örgütsel bağlılık, duygusal bağlılık ve devamlılık bağlılığı olmak üzere iki boyuta ayrılmıştır. Sonuçlar şirket kültürünün ve şirket tarafından çalışanlara verilen değerin duygusal bağlılığı açıkladığını göstermiştir. Ayrıca yaş, kıdem ve cinsiyet değişkenlerinin bağlılık öncülleri ve faklı bağlılık boyutları arasındaki ilişkiyi etkilediğini göstermektedir.
Keywords: Örgütsel Bağlılık; Personel Yönetimi